Determination of inter‐ionic and intra‐ionic interactions in a monofluorinated imidazolium ionic liquid by a combination of X‐ray crystallography and NOE NMR spectroscopy. (28th May 2017) - Lingscheid, Yves; Paul, Mathias; Bröhl, Andreas; Neudörfl, Jörg‐Martin; Giernoth, Ralf
Abstract : We report the very first application of a Transient 1D 1 H 19 F NOE NMR experiment in neat ionic liquids. In comparison with classical 2D HOESY NMR spectroscopy, a substantial reduction in measurement time is gained with comparable quality and information content of the spectra. In combination with classical X‐ray crystallography, we have applied this technique for the determination of inter‐ionic distances (i.e. probabilities of presence) utilizing an ionic liquid containing a monofluorinated imidazolium cation. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A Transient 1D 1 H 19 F NOE NMR experiment has been applied to a monofluorinated ionic liquid to determine inter‐ionic distances. The results have been compared and validated with classical 2D HOESY experiments and the X‐ray crystal structure.